Crónicas periodísticas: relatos e inmigración - Rodríguez Wangüemert, CARMEN (Estudios sobre el Mensaje Periodístico, 2007)
In this study, immigration is a pretext giving a point of focus in order to analyse in depth the narrative used in interpretative journalism. The message is analysed as the centre of informative activity and also as the news report which narrates, explains and shows a reality selected by professional criteria. The study of a selection of articles on immigration in the Canary Islands in 2006 fulfills the main objective of recognizing in this genre the essential features which give identity to and guarantee the future of the news story as the nucleus of journalistic credibility. In addition, the study contextualises the situation in one small part of immigration, which affects around 195 million people worldwide, giving a journalistic point of view to the context opened by different social disciplines for the revision of the concept of citizenship.